Anticipatory Effects on Perceived Pain: Associations With Development and Anxiety. Issue 9 (November 2018) - Michalska, Kalina J.; Feldman, Julia S.; Abend, Rany; Gold, Andrea L.; Dildine, Troy C.; Palacios-Barrios, Esther E.; Leibenluft, Ellen; Towbin, Kenneth E.; Pine, Daniel S.; Atlas, Lauren Y.
ABSTRACT: Objective: Naturalistic studies suggest that expectation of adverse experiences such as pain exerts particularly strong effects on anxious youth. In healthy adults, expectation influences the experience of pain. The current study uses experimental methods to compare the effects of expectation on pain among adults, healthy youth, and youth with an anxiety disorder. Methods: Twenty-three healthy adults, 20 healthy youth, and 20 youth with an anxiety disorder underwent procedures in which auditory cues were paired with noxious thermal stimulation. Through instructed conditioning, one cue predicted low-pain stimulation and the other predicted high-pain stimulation. At test, each cue was additionally followed by a single temperature calibrated to elicit medium pain ratings. We compared cue-based expectancy effects on pain across the three groups, based on cue effects on pain elicited on medium heat trials. Results: Across all groups, as expected, participants reported greater pain with increasing heat intensity (β = 2.29, t (41) = 29.94, p < .001). Across all groups, the critical medium temperature trials were rated as more painful in the high- relative to low-expectancy condition (β = 1.72, t (41) = 10.48, p < .001). However, no evidence of between-group differences or continuous associations with age or anxiety was observed. Conclusions: All participants showed strong effects of expectancy on pain. No influences of development or anxiety arose. Complex factors may influence associations among anxiety, development, and pain reports in naturalistic studies. Such factors may be identified using experiments that employ more complex, yet controlled manipulations of expectancy or assess neural correlates of expectancy.